The Effect of Entrepreneurship Education and Opportunity Recognition On Entrepreneurial Intention Mediated by Entrepreneurial Skills in Double Track Program Students in Lamongan Regency - Arif, Saiful; Fulgentius Danardana Murwani; Heny Kusdiyanti (International Journal of Technology and Education Research, 2025)
Indonesia is a developing country with the fourth largest population in the world, thus having enormous human resource potential. However, this potential has not been fully utilised because many high school graduates do not continue their education, work, or participate in training. One way to prepare high school students in Lamongan Regency to face these challenges is through entrepreneurship education, which is expected to strengthen skills, recognise opportunities, and foster entrepreneurial intent. The research method used is the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). Data analysis techniques use descriptive statistics. The results of the analysis show that: (1) The results of the study indicate that there is a positive and significant effect of entrepreneurial education on entrepreneurial skills, (2) The results of the study indicate that there is no positive and significant effect of opportunity recognition on entrepreneurial skills, (3) The results of the study indicate that there is a direct positive and significant effect of entrepreneurial education on entrepreneurial intention. (4) The results show that there is a direct positive and significant effect between the variables of opportunity recognition and entrepreneurial intention, (5) The results show that there is a direct positive and significant effect of entrepreneurial skills on entrepreneurial intention, (6) The results show that entrepreneurial education has an effect on entrepreneurial intention through entrepreneurial skills. (7) The results show that opportunity recognition does not have an effect on entrepreneurial intention through entrepreneurial skills. The results of this study are expected to encourage schools to strengthen the implementation of entrepreneurial education by providing more practical activities, such as business projects, business incubation programmes, or collaboration with local MSMEs